Language and Color Perception: Evidence From Mongolian and Chinese Speakers - He, Hu; Li, Jie; Xiao, Qianguo; Jiang, Songxiu; Yang, Yisheng; Zhi, Sheng (Frontiers in Psychology, 2019)
The present research contributes to the debates in cognitive sentence on the relationship between language and perception by comparing Mongolian and Chinese speakers’ color perception. Chinese (Mandarin) and Mongolian color terms divide the blue spectrum differently but the green spectrum similarly. In Mongolian, light blue (“qinker”) and dark blue (“huhe”) are strictly distinct, while both light green and dark green are described as one word, nogvgan. In Chinese, however, both light blue and dark blue are simply described by one word, lan, and both light green and dark green are described by a single word, lv. The current study used a free-sorting task and a visual search task to investigate whether this linguistic difference between Chinese and Mongolian speakers leads to a difference in color discrimination. Using the free-sorting task, compared with Chinese speakers, Mongolian speakers exhibited different sorting in the blue region (by distinguishing light and dark blue) and the same sorting in the green region. Further results showed that Mongolian speakers discriminated visual search displays that fall into different linguistic categories in Mongolian (e.g., qinker or huhe) more quickly than visual search displays that belong to the same linguistic category (e.g., both qinker) in a visual search task. Moreover, this effect was disrupted disappeared in participants who Mongolian speakers performed a secondary task engaging involving verbal working memory (but not a task engaging involving spatial working memory), suggesting linguistic interference. Chinese speakers performing the visual search task did not show a such a category advantage under any of the conditions. The finding provides support for the Whorf hypothesis with evidence from an Altay language. Meanwhile, both Chinese and Mongolian speakers reacted faster to the green color than the blue color in the visual search task, suggesting that the variation in human color perception is constrained by certain universal forces. Thus,our findings suggest that our perception is shaped by both relativistic and universal forces and that an eclectic perspective may be adopted..